Histopathological evaluation of abnormal uterine bleeding with immunohistochemical study of significant estrogen receptor expression in endometrium of women with different age groups - Singh, Ankita; Tripathi, Dipti; Singh, Pratima; Agrawal , Sanjay (International Journal of Research in Medical Sciences, 2023)
Background: Abnormal uterine bleeding is symptom, not disease. Bleeding per vaginum is labelled to be pathological when there is constant irregularity in pattern and flow of bleeding, altered duration or increased amount of menstrual blood. Histopathological examination of endometrium biopsies remains a gold standard diagnostic tool. Methods: A prospective study was done on 150 patients presenting with AUB over the period January 2022 to December 2022 in the department of pathology, Hind institute of medical sciences, Sitapur, Uttar Pradesh, India. The sections were stained with hematoxylin and eosin and special stain estrogen receptor was used. Results: Majority of the patients were seen in the perimenopausal age group and most common complaint was menorrhagia in 73 patients (48%). The commonest pathology observed in our study was proliferative phase endometrium in 48 patients (32%). Most of the endometrial carcinoma (4%) were presented after the age of 50 years. The association between histopathological patterns and estrogen receptor category were found to be statistically significant as the p<0.05. Conclusions: Disease burden on a global scale is witnessed by women affected by AUB thus having a detrimental impact. Accurate diagnosis of AUB in women over the age of 35yrs is important to rule out preneoplastic lesions and malignancies so that surgical interventions can be avoided by initiating proper medical management. Comparing the hyperplastic and neoplastic endometrium to that of the proliferative phase, ER expression was lower. Endometrial carcinoma with advanced stage often lacks the expression of the receptors.